Efficacy and survival in patients with cardiac contractility modulation: Long-term single center experience in 81 patients. (15th March 2015) - Kuschyk, Jürgen; Roeger, Susanne; Schneider, Raphaela; Streitner, Florian; Stach, Ksenija; Rudic, Boris; Weiß, Christel; Schimpf, Rainer; Papavasilliu, Theano; Rousso, Benny; Burkhoff, Daniel; Borggrefe, Martin
Abstract: Aims: To analyze long-term efficacy and survival in patients with chronic heart failure treated with cardiac contractility modulation. Methods: 81 patients implanted with a CCM device between 2004 and 2012 were included in this retrospective analysis. Changes in NYHA class, ejection fraction (EF), Minnesota Living with Heart Failure Questionnaire, NT-proBNP and peak VO2 were analyzed during a mean follow up of 34.2 ± 28 months (6–123 months). Observed mortality rate was compared with that predicted by the MAGGIC Score. Results: Patients were 61 ± 12 years old with EF 23 ± 7%. Heart failure was due to ischemic (n = 48, 59.3%) or idiopathic dilated (n = 33, 40.7%) cardiomyopathy. EF increased from 23.1 ± 7.9 to 29.4 ± 8.6% (p < 0.05), mean NT-proBNP decreased from 4395 ± 3818 to 2762 ± 3490 ng/l (p < 0.05) and mean peak VO2 increased from 13.9 ± 3.3 to 14.6 ± 3.5 ml/kg/min (p = 0.1). The overall clinical responder rate (at least 1 class improvement of NYHA within 6 months or last follow-up) was 74.1%. 21 (25.9%) patients died during follow up, 11 (52.4%) due to cardiac conditions and 10 (47.6%) due to non-cardiac conditions. Mortality rates at 1 and 3 years were 5.2% and 29.5% compared to mortality rates estimated from the MAGGIC risk score of 18.4% (p < 0.001) and 40% (p = ns), respectively. Log-Rank analysis of all events through 3 years of follow-up, however, was significantly less than predicted (p = 0.022). Conclusions: CCM therapy improved quality of life, exercise capacity, NYHA class, EF and NT-proBNP levels during long-term follow up. Mortality rates appeared to be lower than estimated from the MAGGIC score.